"Just" ecopreneurs: re-conceptualising green transitions and entrepreneurship. Issue 4 (3rd April 2017) - Affolderbach, Julia; Krueger, Rob
ABSTRACT: Economic, environmental, and social limits of the current capitalist mode of production have led to a rethinking and reconceptualisation of economic processes and models including the role of businesses in sustainable development. While green economies and more specifically green entrepreneurs have been identified as agents of change that can challenge the mainstream and seek to induce environmental, social, and ethical transformation of society, much research has stayed within existing models of thinking predominantly rooted in technocratic approaches (e.g. ecological modernisation and more recently transition studies). This paper seeks to offer an alternative understanding of green entrepreneurship that breaks open these discussions using an environmental justice frame that focuses on the role of extra-economic discourses in shaping the social relations of economic systems. By drawing on an exemplary case study of "just" entrepreneurship from Boston, Massachusetts, USA, the paper seeks to start a conversation around the ideas of green entrepreneurship and environmental justice as vehicles to deliver potentially broader system changes and explores both conceptual and practical aspects of green development. As such, it offers (1) evidence of a just green economy that can be realised within existing capitalist structures as well as (2) a different conceptual entry point to understanding green entrepreneurship.